The genus Anelytra (Orthoptera: Conocephalinae: Agraeciini: Liarina), with one new species from Hainan, China - Shi, Fu-Ming; Xie, Guang-Lin (Zootaxa, 2015)
The paper deals with two species, one is new, Anelytra hainanensis Shi sp. nov. We provide the description and figures of taxonomic characters of the new species and Anelytra compressa Shi & Qiu, 2009. The type material is deposited in the Museum of Hebei University.